2011
DOI: 10.1111/j.1440-1630.2011.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of professional currency: Perceptions of occupational therapists

Abstract: These findings yield some interesting insights into the way therapists think about and structure their professional learning, and provide direction to plan professional development activities based on self-identified need and preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…Warr and Birdi (1998) also confirmed this positive relationship for support from colleagues; however, Maurer and Tarulli (1994) found a negative relationship regarding this support, whereas social integration with colleagues was statistically nonsignificant (Doornbos et al, 2008). Murray and Lawry (2011) concluded that it was important to have people around. In addition, Pierce and Maurer (2009) also found a negative relationship between organizational support and involvement in work-related learning.…”
Section: Antecedents Of Employees' Participation In Work-related Learmentioning
confidence: 74%
See 1 more Smart Citation
“…Warr and Birdi (1998) also confirmed this positive relationship for support from colleagues; however, Maurer and Tarulli (1994) found a negative relationship regarding this support, whereas social integration with colleagues was statistically nonsignificant (Doornbos et al, 2008). Murray and Lawry (2011) concluded that it was important to have people around. In addition, Pierce and Maurer (2009) also found a negative relationship between organizational support and involvement in work-related learning.…”
Section: Antecedents Of Employees' Participation In Work-related Learmentioning
confidence: 74%
“…They stated that training is not attractive if employees cannot use it. This relevancy for practice was also identified by Murray and Lawry (2011).…”
Section: Antecedents Of Employees' Participation In Work-related Learmentioning
confidence: 90%
“…; Townsend et al ., ). Practitioners with master's degrees and continuing competence goals had higher intrinsic motivation for participating in maintenance activities (Strickland, ) and were motivated to maintain their continuing competence ‘because it is beneficial to their wellbeing’ (Murray & Lawry, , p. 266). Regulatory requirements and employers’ expectations also affected practitioners’ perceptions of the need for continuing competence (Mayhan, ; Schumacher, ; Townsend et al .…”
Section: Resultsmentioning
confidence: 99%
“…This finding was surprising because of the many drivers for providing CPD for rural AHP including mandated professional registration requirements, the need to be professionally current [40], and to manage diverse practice demands [4]. Opportunities for engagement in CPD also minimises professional isolation, enhances quality improvement, and supports staff recruitment and retention [17].…”
Section: Discussionmentioning
confidence: 99%